Vorinostat eliminates multicellular resistance of mesothelioma 3D spheroids via restoration of Noxa expression. - GRAY, STEVEN (My University, 2012)
When grown in 3D cultures as spheroids, mesothelioma cells acquire a multicellular resistance to apoptosis that resembles that of solid tumors. We have previously found that resistance to the proteasome inhibitor bortezomib in 3D can be explained by a lack of upregulation of Noxa, the pro-apoptotic BH3 sensitizer that acts via displacement of the Bak/Bax- activator BH3-only protein, Bim. We hypothesized that the histone deacetylase inhibitor vorinostat might reverse this block to Noxa upregulation in 3D. Indeed, we found that vorinostat effectively restored upregulation of Noxa protein and message and abolished multicellular resistance to bortezomib in the 3D spheroids. The ability of vorinostat to reverse resistance was ablated by knockdown of Noxa or Bim, confirming the essential role of the Noxa/Bim axis in the response to vorinostat. Addition of vorinostat similarly increased the apoptotic response to bortezomib in another 3D model, the tumor fragment spheroid, which is grown from human mesothelioma ex vivo . In addition to its benefit when used with bortezomib, vorinostat also enhanced the response to cisplatin plus pemetrexed, as shown in both 3D models. Our results using clinically relevantshow that the manipulation of the core apoptotic repertoire may improve the chemosensitivity of mesothelioma. Whereas neither vorinostat nor bortezomib alone has been clinically effective in mesothelioma, vorinostat may undermine chemoresistance to bortezomib and to other therapies thereby providing a rationale for combinatorial strategies
PUBLISHED
Keywords: 3D models; 3D models